Adsorptive cathodic stripping voltammetry of lead in water samples using 2, 2ʹ-bipyridine or 1,10-phennanthroline and nitrite ions / Masar Hadi Jawad, Azizan Aziz and Sulaiman Ab Ghani. - Jawad, Masar Hadi; Aziz, Azizan; Ab Ghani, Sulaiman (2017)
A differential pulse adsorptive cathodic stripping voltammetric (DPAdCSV) method for the determination of lead levels in water sample by using pairs of ligands (complexing agents) / - nitrite and 1,10 phennanthroline - nitrite were investigated. Variables affecting the response such as pH, supporting electrolyte, deposition potential, deposition time, stirring speed, drop size, sweep rate, pulse amplitude and ligand concentration were studied. Under optimized conditions the relationship between peak current and lead concentration with 2,2ʹ-bipyridine - nitrite and 1,10 phennanthroline - nitrite were linear in the range of 10 - 500 ng mL-1 and 7-500 ng mL-1 with limit of detection of 0.48 ng mL-1 and 0.36 ng mL-1 respectively . The relative standard deviations (RSD) for 9 determinations of 25 ng mL−1 Pb (II) using 2,2ʹ-bipyridine - nitrite and 1,10 phennanthroline - nitrite were 1.74% and 1.84%, respectively. The values obtained for the proposed technique correlated well with those of atomic absorption spectrometry (AAS) as the standard method with correlation coefficient (R2) of 0.9991 and 0.9986. The method was applied for the determination of lead in sea, lake and tap waters. The interferences of other metals and major salts present were negligible except iron (III) and Aluminum (III).